Principles of Forensic Linguistic Research - V. O. Kuznetsov (Теория и практика судебной экспертизы, 2022)
The article reviews the key principles of the forensic linguistic research conducted within the framework of forensic linguistics: linguistic, author’s, forensic analysis of video and sound recordings and examination of intellectual property objects. They are the principles of objectivity, comprehensiveness and completeness of the study, consistency, scientific validity, necessity and sufficiency, verifiability, criteria orientation, accessibility of the description of study process and results. It has been shown that the listed principles represent the guiding ideas, attitudes applied by an expert linguist when conducting expert activities.